Characterization of Electrical Activity in Post-myocardial Infarction Scar Tissue in Rat Hearts Using Multiphoton Microscopy - Ghouri, Iffath A.; Kelly, Allen; Salerno, Simona; Garten, Karin; Stølen, Tomas; Kemi1, Ole-Johan; Smith, Godfrey L. (Frontiers in Physiology, 2018)
Background: The origin of electrical behaviour in post-myocardial infarction scar tissue is still under debate. This study aims to examine the extent and nature of the residual electrical activity within a stabilised ventricular infarct scar. Methods & Results: An apical infarct was induced in the left ventricle of Wistar rats by coronary artery occlusion. Five weeks post-procedure, hearts were Langendorff-perfused and optically mapped using di-4-ANEPPS. Widefield imaging of optical action potentials (APs) on the left ventricular epicardial surface revealed uniform areas of electrical activity in both normal zone (NZ) and infarct border zone (BZ), but only limited areas of low-amplitude signals in the infarct zone (IZ). 2-photon (2P) excitation of di-4-ANEPPS and Fura-2/AM at discrete layers in the NZ revealed APs and Ca2+ transients (CaTs) to 500-600µm below the epicardial surface. 2P imaging in the BZ revealed superficial connective tissue structures lacking APs or CaTs. At depths greater than approximately 300µm, myocardial structures were evident that supported normal APs and CaTs. In the IZ, although 2P imaging did not reveal clear myocardial structures, low-amplitude AP signals were recorded at discrete layers. No discernible Ca2+ signals could be detected in the IZ. AP rise times in BZ were slower than NZ (3.50±0.50ms vs. 2.23±0.28ms) and further slowed in IZ (9.13±0.56ms). Widefield measurements of activation delay between NZ and BZ showed negligible difference (3.37±1.55ms), while delay values in IZ showed large variation (11.88±9.43ms). Conclusion: These AP measurements indicate that BZ consists of an electrically inert scar above relatively normal myocardium. Discrete areas/layers of IZ displayed entrained APs with altered electrophysiology, but the structure of this tissue remains to be elucidated.